Unemployment among Technical Students: Implication for Managers of Higher Education - Sunday Rufus Olojuolawe; Osuntuyi Olusola Edward; Ibidapo Bamidele Abel (Universitas Diponegoro, 2022)
The problem of unemployment among youths has remained unabated. This has cast doubt on the methods of instructions by lecturers. This study takes a critical review of some of the previous studies with an emphasis on employment statistics and employability skills. The paper x-ray the basic elements of employability skills and the latest statistics of youth unemployment in Africa particularly, Nigeria. The aim is to sensitize education managers of higher institutions in Nigeria about the danger inherent in turning out graduates massively without the corresponding skills to match them adequately with the world of work. Findings show that there is a persistent rise in the rate of youth unemployment because what the schools offered is not compliant with the labour market demand. The resulting skills played a significant role in increasing unemployment among Tertiary Education graduates. Therefore, the higher education curriculum needs to be modified to reflect the skills required of employers.